191 MOBILE/ENHANCE integrated efficacy analysis of PR-fampridine. Issue 12 (14th November 2019) - Hupperts, Raymond; Hobart, Jeremy; Gasperini, Claudio; Lycke, Jan; Ziemssen, Tjalf; Feys, Peter; McNeill, Manjit; Acosta, Carlos
Abstract : Introduction: The MOBILE and ENHANCE studies evaluated prolonged-release fampridine (PR-FAM) vs placebo (MOBILE, n=68 vs 64; ENHANCE, n=315 vs 318) in people with multiple sclerosis (PwMS) over 24 weeks. PR-FAM-associated improvements in walking and physical performance were assessed using an integrated efficacy analysis. Methods: Pooled analyses of MOBILE/ENHANCE included the proportion of PR-FAM–treated PwMS with pre-specified threshold improvement in MSWS-12 and in Timed Up and Go (TUG) speed, and mean changes from baseline in MS Impact Scale physical subscale (MSIS-29 PHYS) and Berg Balance Scale (BBS). Results: Over 24 weeks, significantly more PR-FAM–treated PwMS achieved ≥8-point mean improvement in MSWS-12 (44.3% vs 33.0%; OR: 1.68 [95%CI: 1.23, 2.29]; P<0.001) and ≥15% mean improvement in TUG speed (44.1% vs 34.5%; OR: 1.54 [95%CI: 1.13, 2.11]; P=0.007) vs placebo. Significant improvements from baseline were also registered in MSIS-29 PHYS (least square mean [LSM] difference: −3.18 [95%CI: −4.84, −1.52]; P<0.001) and BBS (LSM difference: 0.62 [95%CI: 0.09, 1.14]; P=0.021) vs placebo. Conclusions: This post-hoc pooled analysis strengthens evidence that PR-FAM produces clinically meaningful improvements in self-reported walking and benefits self-reported physical function, mobility, balance, and quality of life over 24 weeks for PwMS. Support: Biogen. Disclosures to be included on poster.